Islam and Coastal Culture: A Study of Symbolic Meaning in the Tradition of Sedekah Laut in Rembang, Central Java - Siti Rohwati; Al Mudzill Al Mudzill; Ainul Mamnuah (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2025)
This article reveals the tradition of Sedekah Laut in Rembang, Central Java, by placing it as a manifestation of coastal Islam built through the symbolic meaning of rituals. This study focuses on how ritual symbols are understood, experienced, and interpreted for religious meaning by coastal Muslim communities. Using qualitative methods and an ethnographic approach, data was collected through participant observation, in-depth interviews, and documentation. The analytical framework of this study is based on Clifford Geertz's theory of symbolic interpretation, which seeks to understand symbols as vehicles of historical and contextual meaning through which humans understand and communicate cultural patterns, worldviews, and values in depth. He emphasizes the importance of symbolic interpretation in understanding culture and the meaning behind social and religious practices. The results of the study show that Sedekah Laut, known as Larung Sesaji, is not interpreted by the community as a religious compromise, but rather as a symbolic medium for structuring the relationship between humans, God, and the sea in the lives of coastal communities. Ritual elements such as miniature houses, goat heads, market snacks, flowers, coconuts, and cigarettes are not understood as offerings in the sense of worship, but as cosmological symbols that represent the continuity of life, safety, and ecological attachment that are legitimized religiously. Thus, researchers argue that the sustainability of Sedekah Laut relies on the symbolic function of rituals in shaping contextual religious experiences, rather than on the normative negotiation process between religious teachings and local traditions.